2017
DOI: 10.3390/md15070226
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Microcystin (LR, RR and YR) in Three Freshwater Bivalves in Microcystis aeruginosa Bloom Using Dual Isotope Tracer

Abstract: Stable isotope tracers were first applied to evaluate the Microcystis cell assimilation efficiency of Sinanodonta bivalves, since the past identification method has been limited to tracking the changes of each chl-a, clearity, and nutrient. The toxicity profile and accumulation of MC-LR, -RR and -YR in different organs (foot and digestive organs) from the three filter-feeders (Sinanodonta woodiana, Sinanodonta arcaeformis, and Unio douglasiae) were assessed under the condition of toxigenic cyanobacteria (Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The amount of toxin accumulated will depend on several factors associated to toxin intake and the mechanisms of detoxification specific for each species. For instance, in an in situ pond experiment during a M. aeruginosa bloom, three freshwater bivalves showed different MCs accumulation in muscle and digestive gland tissues according to grazing, assimilation and detoxification capacities of each mollusc [45]. Nevertheless, most of the studies dealing with cyanotoxins dynamics in bivalves have been done under controlled laboratory conditions with individual cyanobacteria species.…”
Section: Mussel Contaminationmentioning
confidence: 99%
“…The amount of toxin accumulated will depend on several factors associated to toxin intake and the mechanisms of detoxification specific for each species. For instance, in an in situ pond experiment during a M. aeruginosa bloom, three freshwater bivalves showed different MCs accumulation in muscle and digestive gland tissues according to grazing, assimilation and detoxification capacities of each mollusc [45]. Nevertheless, most of the studies dealing with cyanotoxins dynamics in bivalves have been done under controlled laboratory conditions with individual cyanobacteria species.…”
Section: Mussel Contaminationmentioning
confidence: 99%
“…in the mussel. This concentration was selected taking into account those reported in the literature for MCs (Kim et al, 2017;Turner et al, 2018) and CYN (Saker et al, 2004) in bivalves. Then, 3 of these samples were cooked by steaming for 2 min, as described in Guzmán-Guillén et al (2017), once the water began to boil (100ºC), and afterwards they were submitted to the in vitro digestion model to assess toxins bioaccessibility (see section 2.3).…”
Section: Experimental Setup and Sample Treatmentmentioning
confidence: 99%
“…The main route of exposure to these toxins is by consumption of contaminated water, although it can also occur through the intake of food (fish, shellfish or vegetables) or cyanobacterial food supplements contaminated with cyanotoxins (Buratti et al, 2017). In fact, several authors have reported accumulation of MCs (Vasconcelos, 1995;Vareli et al, 2012;Gibble et al, 2016;Baralla et al, 2017;Kim et al, 2017) and CYN (Anderson et al, 2003;Saker et al, 2004) in mussels, resulting in potential human risks after their consumption (Ibelings and Chorus, 2007;Gutiérrez-Praena et al, 2013;Testai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sinanodonta bivalves had a larger effect on the primary productivity of toxic cyanobacteria, demonstratinga more realistic achievement for biomanipulation. Also, Sinanodonta (S. arcaefomis and S. woodiana) should incorporate more toxic cyanobacteria cells than U. douglasiae, probably due to its larger detoxification capacity (Kim et al, 2017b). As a result, S. arcaefomis and S. woodiana could be useful organisms to reduce massive toxic cyanobacteria blooms in eutrophic agricultural reservoirs and lakes.…”
Section: Comparing Grazing By Differential Sinanodonta Bivalve Speciesmentioning
confidence: 99%
“…On the contrary, and Kim et al (2017a) argued that filterfeeding marcroinvertebrate (Caridina denticulate) as native species can easily reduce to blue-green algae than planktivore fishes, as a results, cyanobacteria accumulations might constitute up to 69% of biomass carbon in freshwater atyid shrimp (Peristemia australiensis) (Piloa et al, 2008). In addition, the use of bivalve species (Unionids) which is contribute to bio-control of eutrophication through bio-filter effectiveness by reducing algal biomass (Reeders et al, 1990;Soto et al, 1999;Kim et al, 2017b) are probably more suitable for shallow lake which mainly consist of soft substrate (mixture of mud and sand) instead of zebra mussel which is require hard substrate for settlement, with their high filtration rates on phytoplankton have been promoted as a tool in biomanipulation of lakes (Reeders et al, 1990). Also, aquatic plants are themselves part of the food web, and could be control massive algae bloom through competing for nutrients and other resources with phytoplankton and periphyton (Ozimek et al, 1990;van Donk et al, 1993 An et al, 2010).…”
Section: Introductionmentioning
confidence: 99%